GENDING SANDYAGITA KARYA I WAYAN SENEN TINJAUAN BENTUK DAN FUNGSI - Putri Wulandari (Institut Seni Indonesia Yogyakarta, 2017)
I Wayan Senen is a composer who has a created of the gending sandyagita as a religious gending for Hinduist activities in Yogyakarta. There are several factors of the created gending-gending sandyagita is internal factors and external factors. Which included in internal factors is the desire of achivement, would like to adoption the creation method of Wayan Beratha, and donate the result of artworks. Which included in external factors is birth of a phenomenon, social interaction and a request from an event. In the creation gending sandyagita of Senen, has a mix of karawitan Jawa dan karawitan Bali. Karawitan Jawa is used as a source of design among other forms of gending sampak, vocal melody macapat pangkur, pattern of tabuhan gamelan sekaten, and the main melody vocal panjang ilang. The gamelan creation that used in sandyagitafor Senen is gamelan Semarandana. The method of used in this research is qualitative research. Gending sandyagita has three function, there are ritual ceremoni, entertaiment, and estetic presentation.